Short term methylphenidate treatment does not increase myocardial injury in the ischemic rat heart - Seeley, S. L; D'Souza, M. S; Stoops, T. S; Rorabaugh, B. R (Physiological research, 2020)
Methylphenidate is commonly used for the treatment of attention deficit hyperactivity disorder. The cardiovascular safety of methylphenidate has been a subject of debate with some studies indicating that methylphenidate increases the likelihood of experiencing a myocardial infarction. However, it is unknown whether methylphenidate worsens the extent of injury during an ischemic insult. The purpose of this study was to determine whether short term exposure to methylphenidate increases the extent of myocardial injury during an ischemic insult. Male and female rats received methylphenidate (5 mg/kg/day) or saline for 10 days by oral gavage. Hearts were subjected to 20 min of ischemia and 2 h of reperfusion on a Langendorff isolated heart apparatus on day 11. Cardiac contractile function was monitored via an intraventricular balloon and myocardial injury was assessed by triphenyltetrazolium chloride staining. Methylphenidate significantly increased locomotor activity in male and female rats, confirming absorption of this psychostimulant into the central nervous system. Male hearts had significantly larger infarcts than female hearts, but methylphenidate had no impact on infarct size or postischemic recovery of contractile function in hearts of either sex. These data indicate that methylphenidate does not increase the extent of injury induced by an ischemic insult.
Keywords: obnova funkce; stimulanty centrálního nervového systému; Central Nervous System Stimulants; krysa rodu Rattus; kontrakce myokardu; mužské pohlaví; Methylphenidate; ischemická choroba srdeční; Animals; infarkt myokardu; Myocardial Contraction; ženské pohlaví; zvířata; methylfenidát; rozvrh dávkování léků; Female; Drug Administration Schedule; Myocardial Ischemia; modely nemocí na zvířatech; Myocardial Infarction; Recovery of Function; Male; Rats, Sprague-Dawley; Rats; Disease Models, Animal; potkani Sprague-Dawley